2004
DOI: 10.1002/jssc.200301620
|View full text |Cite
|
Sign up to set email alerts
|

Approaches to identifying and quantifying polycyclic aromatic hydrocarbons of molecular weight 302 in diesel particulates

Abstract: Among the PAH class of compounds, high molecular weight PAH are now considered as relevant cancer inducers, but not all of them have the same biological activity. However, their analysis is difficult, mainly due to the presence of numerous isomers and due to their low volatility. Retention indices (Ri) for 13 dibenzopyrenes and homologues were determined by high-resolution capillary gas chromatography (GC) with four different stationary phases: a 5% phenyl-substituted methylpolysiloxane column (DB-5 ms), a 35%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 29 publications
0
15
0
1
Order By: Relevance
“…Detection and separation of D[ a,l ]P and other DBPs in Beijing PM were confirmed using authentic standards of structural isomers known to co-elute using traditional chromatography methodologies 7,10,11. Over 20 isomers with a m / z of 302 were baseline separated from SRM 1649b (urban dust) and from Beijing PM.…”
Section: Resultsmentioning
confidence: 87%
“…Detection and separation of D[ a,l ]P and other DBPs in Beijing PM were confirmed using authentic standards of structural isomers known to co-elute using traditional chromatography methodologies 7,10,11. Over 20 isomers with a m / z of 302 were baseline separated from SRM 1649b (urban dust) and from Beijing PM.…”
Section: Resultsmentioning
confidence: 87%
“…Are they frequently recorded or only rarely, and are they very (site-)specific compounds? Above, the dibenzopyrene isomers were mentioned as highly toxic PAHs that may be relevant for inclusion on any list of environmentally significant PAHs, but up to today no more than some 40 studies report the detection of these compounds in environmental samples: their presence in the environment has been shown in vehicle exhaust (31)(32)(33)(34)(35)(36)(37), air particulate matter (36,(38)(39)(40)(41)(42), house dust (43), coal tar (31,40,44), coal extracts (7), automobile tires (45), particulates from coal combustion (46,47), fly ash (48), sediment and soil (31,40,(49)(50)(51)(52)(53)(54)(55), cigarette smoke (34), and exhaust gases from sewage sludge incineration (56).…”
Section: Other Pah Lists and Relevance Of The Dibenzopyrenesmentioning
confidence: 99%
“…Although high molecular mass PAHs (molecular mass >300) are not routinely quantified, a number of studies have reported their determination in coal tar and fuel combustion exhaust [22 -24] as well as in environmental samples such as mussels and sediments [23 -25]. Schubert et al [17] and Sauvain and Vu Duc [26] investigated the separation of the m/z 302 isomers in different stationary phases with different polarities including 5% phenyl methyl polysiloxane, 50% phenyl methyl polysiloxane and liquid crystalline stationary phases. The use of 50% phenyl-substituted stationary phases provided a better separation compared to 5% phenyl-substituted ones, while the use of the liquid crystalline column provided a unique selectivity due to the particular retention behaviour on this stationary phase [17].…”
Section: Selectivity In the Presence Of Interfering Compoundsmentioning
confidence: 99%